2014
DOI: 10.2495/sc140511
|View full text |Cite
|
Sign up to set email alerts
|

The identification and classification of green areas for urban planning using multispectral images at Baja California, Mexico

Abstract: In the legal framework of urban planning in Mexico, the provision of urban green areas is approached from a social perspective, as public spaces for recreation and sports activities, regardless of the environmental and economic benefits they can provide from a sustainable development perspective. The planning of urban green areas requires a set of conditions in order to be successful, among which are: an updated regulatory framework, adequate financial resources, technical knowledge of the appropriate plant sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…It refers to any green spaces, including the permeable hard-surface areas, mainly consisting of "soft surfaces", such as vegetation and soil [4]. Urban green space exists in a broad variety, such as sport fields, parks, residential green spaces, city farms, greenways, private green areas, and agricultural areas [5]. It is ecological land dominated by natural and artificial vegetation in cities, plays a particular role in the structure of the urban regions [6], and adjusts the urban climate and improves human settlements by affecting the energy and water exchange between the near-surface atmosphere and the underlying surface [7].…”
Section: Introductionmentioning
confidence: 99%
“…It refers to any green spaces, including the permeable hard-surface areas, mainly consisting of "soft surfaces", such as vegetation and soil [4]. Urban green space exists in a broad variety, such as sport fields, parks, residential green spaces, city farms, greenways, private green areas, and agricultural areas [5]. It is ecological land dominated by natural and artificial vegetation in cities, plays a particular role in the structure of the urban regions [6], and adjusts the urban climate and improves human settlements by affecting the energy and water exchange between the near-surface atmosphere and the underlying surface [7].…”
Section: Introductionmentioning
confidence: 99%
“…Some authors have made spatial inventories of urban green spaces considering these parameters and from these have developed and evaluated a series of indicators that have made it possible to know the situation of this strategic environmental resource in cities. For example, assessments of urban green space of some Mexican cities through the use of geographic information systems have concluded that there is an inadequate provision of green areas per capita as a result of poor urban planning (Peña-Salmón et al, 2014;Ruiz-Luna et al, 2019). Another series of studies has been oriented to estimate its distribution by political-administrative unit (Checa-Artasu, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Different countries may have similar or different type of urban green spaces which depends on location, geography, socio-economic, environment and culture of a particular country (e.g Dunnett et al, 2002;Senanayake et al, 2013;Vatseva et al, 2016;Zhang et al, 2007a). The type of urban green spaces are commonly stated in the set of federal, state and, district or municipal regulatory framework (i.e law and regulation) related to urban planning (Dunnet et al, 2002;Peña-Salmón et al, 2014). However, their definition and characteristic are inconsistent or not standardize between states, districts or even in different administrative or management zones of a city (e.g Badiru et al, 2005;Peña-Salmón et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The type of urban green spaces are commonly stated in the set of federal, state and, district or municipal regulatory framework (i.e law and regulation) related to urban planning (Dunnet et al, 2002;Peña-Salmón et al, 2014). However, their definition and characteristic are inconsistent or not standardize between states, districts or even in different administrative or management zones of a city (e.g Badiru et al, 2005;Peña-Salmón et al, 2014). In the context of sustainable urban planning the inconsistency may cause urban green spaces planning and management not efficient and possibly fail to achieve sustainable urban development.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation